2015
DOI: 10.1016/j.eatbeh.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

UnAdulterated — Children and adults' visual attention to healthy and unhealthy food

Abstract: ObjectiveVisually attending to unhealthy food creates a desire to consume the food. To resist the temptation people have to employ self-regulation strategies, such as visual avoidance. Past research has shown that self-regulatory skills develop throughout childhood and adolescence, suggesting adults' superior self-regulation skills compared to children.MethodsThis study employed a novel method to investigate self-regulatory skills. Children and adults' initial (bottom-up) and maintained (top-down) visual atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…In fact, it has been shown that although both children and adults are attracted to unhealthy food, adults-unlike children-are able to shift their attention away from unhealthy food. 22 In addition, knowledge about healthy foods may guide the food choices of adults more than those of children. In any case, parents are responsible for the foods available at home, and empty-calorie foods at home may also describe parents' own preferences rather than those of their children.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that although both children and adults are attracted to unhealthy food, adults-unlike children-are able to shift their attention away from unhealthy food. 22 In addition, knowledge about healthy foods may guide the food choices of adults more than those of children. In any case, parents are responsible for the foods available at home, and empty-calorie foods at home may also describe parents' own preferences rather than those of their children.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing children to adults, adults are initially strongly attracted by unhealthy foods, but they shift their attention from the unhealthy to the healthy foods, suggesting a self-regulation process of avoidance when measured in with naturalistic viewing paradigm [ 25 ]. Children, on the contrary, attend more strongly to unhealthy foods and do not shift their attention away [ 26 ]. In older adults and elderly, food cue sensitivity has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neuroimagery studies, such as one conducted by Meer et al (2016) [52], found that low nutritional value foods elicit more attention than high nutritional value foods, and for children, they have a higher level of activation in the areas involving reward, motivation and memory while viewing low nutritional value foods. Visual attention studies with eye-tracking cameras [53,54] showed that children pay more attention to low nutritional value foods compared to high nutritional value foods. Implicit affective evaluation studies, such as one by Woodward and Treat (2015) [55], indicated that both added fat and added sugar are associated with more positive affective evaluations.…”
Section: Discussionmentioning
confidence: 99%